SPE EUROPEC/EAGE Annual Conference and Exhibition 2010
DOI: 10.2118/131525-ms
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Petrophysical Properties of a Carbonate-rich Caprock for CO2 Geological Storage Purposes

Abstract: Prior to any CO 2 geological storage operation, the caprock's ability to prevent CO 2 leakage must be carefully assessed. This ability is primarily related to the caprock's pore structure and to the interfacial properties of the caprock and the fluids in place, namely the brine that imbibes the caprock and the CO 2 stored in the underlying reservoir. This paper reports an experimental effort to characterize some of these parameters, using as a working example the carbonate-rich caprock and reservoir conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…The measurement principle is identical, but the experimental setup and procedures have been improved, allowing the investigation of higher temperatures, pressures, and brine salinities, as well as of another acid gas, H 2 S. In addition to quartz and mica, other substrates are examined, including calcite and a carbonate-rich caprock sample coming from an actual CO 2 storage site. Part of these results has been communicated at various conferences (Shah et al 2008a;Tonnet et al 2008Tonnet et al , 2010.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…The measurement principle is identical, but the experimental setup and procedures have been improved, allowing the investigation of higher temperatures, pressures, and brine salinities, as well as of another acid gas, H 2 S. In addition to quartz and mica, other substrates are examined, including calcite and a carbonate-rich caprock sample coming from an actual CO 2 storage site. Part of these results has been communicated at various conferences (Shah et al 2008a;Tonnet et al 2008Tonnet et al , 2010.…”
Section: Introductionmentioning
confidence: 88%
“…Its porosity is below 5% and its permeability in the nanoDarcy range (Tonnet et al 2010(Tonnet et al , 2011. They also include a 'real' carbonate-rich substrate drilled from the caprock of the Rousse depleted gas field in the South-West of France, where about 100 000 tons of CO 2 coming from an oxy-boiler on the nearby industrial Lacq platform are currently being injected over a 2-to 3-year period.…”
Section: Substratesmentioning
confidence: 99%
See 2 more Smart Citations
“… Dickson et al [2006] and Yang et al [2008] found values of the advancing contact angle close to 90° on limestone and chemically treated glass surfaces, again implying neutral wettability with little trapping. However, several other authors [ Chiquet et al , 2007; Espinoza and Santamarina , 2010; Tonnet et al , 2010; Shah et al , 2008] found lower contact angles on quartz, mica and caprock surfaces: although the contact angle is a function of temperature and pressure, at super‐critical conditions CO 2 remained the non‐wetting phase. We address this ambiguity by measuring directly the physical quantities of interest: namely the amount of capillary trapping for the full range of initial saturation – the trapping curve – and the primary drainage capillary pressure on a Berea sandstone core, representative of aquifer rocks.…”
Section: Introductionmentioning
confidence: 96%